Studi Etnobotani Tumbuhan Obat Masyarakat Bumi Pajo - Nehru; Komariah; Ardianto; Ira Rismayana; Nikman Azmin (JUSTER : Jurnal Sains dan Terapan, 2024)
This research aims to study the use of medicinal plants in the community as one of the community's healing traditions in Bumi Pajo Village, Donggo District, Bima Regency as well as the traditional medicinal plant processing methods used by the people of Bumi Pajo Village, Donggo District, Bima Regency. As a type of qualitative research, this research has four informants: village heads, community leaders, religious leaders, and medicine makers. Data collection methods use observation, interviews and documentation. Data analysis consists of three stages: data reduction, data display, and drawing conclusions. This study found that the use and management of traditional medicinal plants in Bumi Pajo Village has been passed down from generation to generation. Medicinal plants are processed in various ways, such as boiling, pounding, steaming, pounding, grinding, grating, and kneading in water. Recommendations from this research are (1) The use of medicinal plants must be maintained and taught to the next generation (2) In the process of consuming plants medication by the people of Bumi Pajo Village, care needs to be taken in determining the amount of medication that can be used to prevent or treat disease (3) This is necessary because it is hoped that this will enable researchers to study more factors related to the use of traditional medicine, especially relating to local communities in certain areas.